Safety and Capacity Performances of Single-lane Right Exit Ramp on Freeway: A Case Study in Jiangsu Province, China. (2016) - Xie, Junping; Ma, Yongfeng; Yuan, Li; Zhang, Peng; Liu, Yan
Abstract: Growing traffic in China has resulted in a demand for freeway exit ramps with higher capacity in order to avoid congestion. The right single-lane exit ramp is the most common style of the freeway exit ramp which can be divided into two types: taper-type single-lane exit ramp and parallel-type single-lane exit ramp. The main objective of the paper was to elaborate recommendations about the best single-lane exit ramp layout according to different parameters by evaluating safety and capacity. 6 taper-type and 4 parallel-type exit ramps were selected in Jiangsu Province and the space mean speeds ( SMS ) of the 200 vehicles on the deceleration lane of each sample were observed. The average SMS standard deviation of taper-type was 8.0 kmph comparing with 4.6 kmph of parallel-type, which indirectly indicated that parallel-type single-lane exit ramp was safer than the other one. The capacities of the two exit ramp types were analyzed using the FHWA 's Traffic Software Integrated System ( TSIS ). Two microsimulation models were constructed and the vehicle input varied from 0 to system alert "backed up" by each increment of 100 pcph . The capacity was defined as the input value before the system "backed up". The results of the two exit ramp types were 1800 pcph and 2100 pcph, which meant the capacity of parallel type was more than the taper type.